O uso de modelos de séries temporais na previsão orçamentária na área de tecnologia de informação - Queiroz, Zandra Cristina Lima Silva (2014)
This study investigated the use of time series models for budget forecasting of IT, in order to find what the appropriateness of using the model for time series to improve the assertiveness of the budget forecast information technology area of a retail company cars in Minas Gerais. By the difficulty that the IT departments of companies face in controlling spending and justify the costs, through the budget, envisioned the possibility of establishing measures and goals that they wish to be fulfilled as it was planned, also allowing the IT manager anticipate expenditures, costs and investments and thus ensure business benefits through its proper use. Because it is a widely used tool, it is noted in the literature an evolution of the concept and form of budgeting, generating both the academic and business world, studies that aim to elucidate the changes in concepts and forms of budget. Regarding the use of the budget, the literature states that the budget is an important tool for planning and for building planning, forecasting is an important ally for the projection of future information. The methodology of the study is descriptive, with quantitative approach using survey data of the IT budget used by a company in the period 2008 to 2013. It might verify that the use of models for time series showed partial assertiveness for variables monthly costs and variable costs. Regarding the investment variable, it was observed that the use of mathematical models has not contributed to improving assertiveness, and results indicate that the use of qualitative prediction is more suitable for this variable. These results do not restrict the use of such methodologies will assist in planning and decision making process of the companies, but serve as input to complement the existing in order to demonstrate to managers the application of mathematical models by series literature, which can be used to budget forecasts, contributing to the operational planning and control of organizations